2020
DOI: 10.1200/jco.19.02408
|View full text |Cite|
|
Sign up to set email alerts
|

Nonmyeloablative Alternative Donor Transplantation for Hodgkin and Non-Hodgkin Lymphoma: From the LWP-EBMT, Eurocord, and CIBMTR

Abstract: PURPOSE To compare the outcomes of patients with Hodgkin or non-Hodgkin lymphoma undergoing nonmyeloablative haploidentical or unrelated cord blood (UCB) hematopoietic cell transplantation. PATIENTS AND METHODS We retrospectively studied 740 patients with Hodgkin lymphoma (n = 283, 38%) and non-Hodgkin lymphoma (n = 457, 62%) age 18-75 years who received transplantations from 2009 to 2016. Data were reported to the Lymphoma Working Party of the European Society for Blood and Marrow Transplantation, Eurocord, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
2
29
0
4
Order By: Relevance
“…Results of this study are actually in line with the one actually reported in the literature, such as the one from Kanate or Fatobene [6,7]. So actually, no differences were actually found in terms of overall survival and leukemia-free survival between haploidentical transplant and HLA (human leukocyte antigen)-identical donor.…”
Section: Podcast Transcriptsupporting
confidence: 89%
“…Results of this study are actually in line with the one actually reported in the literature, such as the one from Kanate or Fatobene [6,7]. So actually, no differences were actually found in terms of overall survival and leukemia-free survival between haploidentical transplant and HLA (human leukocyte antigen)-identical donor.…”
Section: Podcast Transcriptsupporting
confidence: 89%
“…35 Moreover, a recent CIBMTR-EBMT-Eurocord joint study also evidenced worse OS in UCBT recipients (66% of whom received at least one 4 of 6 HLA-matched UCB unit, all with TNC dose .3.0 3 10 7 /kg) compared with haploidentical transplantation recipients attributable to higher rates of acute and chronic GVHD and TRM. 36 Hence, if UCB units meeting these criteria cannot be found, one might consider haploidentical transplantation, particularly in case of availability of haploidentical donors who are young and the recipient's siblings/children. 37 Our study has other relevant limitations, the first being that it was a retrospective cohort analysis in which UCB unit choice was physician dependent and/or institutional preference and possibly dependent on unmeasured factors.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the high rate of severe CRS observed in our cohort may be related to the unique combination of using PBSC grafts with FluMel conditioning. One recent study found a higher rate of NRM and decreased OS in patients with NHL receiving FluMel conditioning for allogeneic HCT compared to udarabine and busulfan-based conditioning 13 , whereas another cohort of patients with lymphoma undergoing haplo-HCT with udarabine and cyclophosphamide conditioning did not suffer increased NRM or reduced OS 14 .…”
Section: Discussionmentioning
confidence: 99%